A novel tunable blue-green-emitting CaGdGaAl2O7:Ce3+, Tb3+ phosphor via energy transfer for UV-excited white LEDs1. Issue 17 (7th May 2015) - Liang, Chao; You, Hongpeng; Fu, Yibing; Teng, Xiaoming; Liu, Kai; He, Jinhua
<x xml:space="preserve">Abstract</x> By tuning the relative content of the doped ions, tunable blue-green emission can be obtained by irradiation at 365 nm.